Novel t(1;8)(p31.3;q21.3) NFIA-RUNX1T1 Translocation in an Infant Erythroblastic Sarcoma: Building a Case for a Rare Genetically Defined Entity. Issue 1 (14th December 2020) - King, Rebecca L; Siaghani, Parwiz J; Wong, Katy; Edlefsen, Kerstin; Shane, Lisa; Howard, Matthew T; Reichard, Kaaren K; Mai, Ming; Viswanatha, David S; Greipp, Patricia T; Goble, Tony A; Ruiz, Maritza; et al.
Abstract: Objectives: Pure erythroid leukemia (PEL) is exceptionally rare in the pediatric setting. Four pediatric PEL cases with t(1;16)(p31;q24) NFIA-CBFA2T3 were reported previously. We present a case of an infant with PEL presenting with erythroblastic sarcoma and harboring a novel t(1;8)(p31.3;q21.3) NFIA-RUNX1T1 fusion detected by RNA sequencing and conventional karyotype. Methods: Bone marrow (BM) and abdominal mass biopsies from the patient were evaluated with extensive immunohistochemical, flow cytometric, cytogenetic, and molecular studies. Results: The patient was a female infant who presented between 2 and 5 months of age with cytopenias and an enlarging abdominal mass. Blasts in the BM and abdominal mass expressed CD71 and CD117 with focal expression of CD43, E-cadherin, epithelial membrane antigen, and hemoglobin A. They were negative for additional myeloid, lymphoid, and nonhematolymphoid markers. These findings were most consistent with PEL and erythroblastic sarcoma. RNA sequencing revealed the novel NFIA-RUNX1T1 fusion. Conclusions: Along with the previously reported PELs with NFIA-CBFA2T3 fusions, we describe a subset of PELs that occur in children, that frequently display extramedullary disease, and that harbor rearrangements of NFIA with core binding factor genes. We hypothesize that, together, these cases represent a rare but distinct clinicopathologic group of pediatric PELs with recurrent genetic abnormality.